Conductive paste for membrane material transfer printing, preparation method, application and solar cell

By adjusting the organic carrier ratio of the conductive paste, optimizing its fluidity and filling ability, the problem of poor silver paste residue and filling during film transfer is solved, and efficient silver paste filling and clean battery surface is achieved, reducing silver consumption and improving battery performance.

CN119889764AActive Publication Date: 2025-04-25CHANGZHOU JUHE NEW MATERIAL CO LTD
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202510354100.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-25
Estimated Expiration
2045-03-25

AI Technical Summary

Technical Problem

The prior art has problems such as silver paste residue, poor filling and gate lines falling off during the film transfer process, resulting in increased silver consumption, reduced battery photoelectric efficiency and increased cost.

Method used

By adjusting the organic carrier ratio of the conductive paste, including an appropriate amount of silicone oil, elastomer and adhesive, the fluidity and filling capacity of the paste are optimized, ensuring high filling rate and good adhesion of the paste in extremely narrow linewidth molds.

Benefits of technology

The high filling rate of conductive paste in film transfer and a clean battery surface is achieved, which reduces silver consumption and line resistance, and improves the photoelectric efficiency and cost-effectiveness of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119889764A_ABST
    Figure CN119889764A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of conductive paste, and provides conductive paste for membrane material transfer printing, a preparation method, application and a solar cell. The conductive paste comprises conductive powder, glass powder and an organic carrier; wherein the organic carrier comprises 0.1-0.5 wt% of an adhesive, silicone oil, 0.1-2 wt% of an elastomer, 0-0.9 wt% of an auxiliary agent, 3-7 wt% of a solvent and 2-7 wt% of a plasticizer calculated by taking the conductive slurry as a base number; the elastomer is SEBS or SEBS modified elastomer or SEPS or SEPS modified elastomer, the silicone oil is polymethyl silicone oil or other modified silicone oil, and the mass content of the silicone oil is 0.5-0.7%; the adhesive comprises cellulose acetate butyrate, ethyl cellulose and polyvinyl butyral, and the combined adhesive can achieve good rheological property of the slurry. According to the invention, by adjusting the ratio of the organic carrier of the slurry, good filling capability of the slurry is obtained, meanwhile, the slurry can adapt to a mold with extremely narrow line width to obtain an excellent height-width ratio of an electrode, the adhesion of the slurry to a membrane material is well overcome, good fluidity is obtained, and meanwhile, a clean battery surface is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of conductive pastes, and in particular relates to a conductive paste for film material transfer, a preparation method, an application, and a solar cell. Background Art

[0002] With the development of the PV industry, the silver consumption of photovoltaic silver paste has increased rapidly, further pushing up the international silver price and restricting the further reduction of LCOE. Patent CN111987175B provides a method for preparing photovoltaic cell electrodes that can effectively reduce silver consumption, namely: fix the battery cell on the carrier of the transfer equipment and apply the transfer solvent, then start the electrode grid line mold above the carrier, and then prepare the film material mold to be filled with silver paste, and then fill the silver paste into the groove area of ​​the corresponding mold, and the mold film material is thermally decomposed during the sintering process to prepare the silver grid line electrode; Patent CN112018197B only provides a method for preparing a film electrode mold. Taking into account the differences in electrode construction methods, there will actually be other demands for this type of silver paste than silk-screen electrodes. It is certain that this construction method will have certain risks in practice: first, there is a risk of residual silver paste in the non-groove area of ​​the mold. After sintering, the residual silver paste will contaminate the battery surface, increase the silver paste consumption, and block light, reduce the battery photoelectric efficiency, and increase the battery unit watt cost; second, in order to achieve the narrow line requirements of screen printing, the existing silver paste has high requirements for thixotropy and has a certain impact on flow in organic design. The filling rate of the paste to the mold is relatively low, and there is even a risk of broken grid if the filling is not good; third, due to the presence of organic film material between the electrode and the mold, the decomposition of the film material during the sintering process will deteriorate the adhesion between the silver paste electrode and the velvet surface, causing the grid line to fall off.

[0003] Of course, as described in the previous patent, the construction method of this type of electrode can achieve extremely fine gate line electrodes, and sintered electrode line widths of less than or equal to 15um or less than 10um are possible, but there is currently no conductive silver paste that is particularly suitable for film transfer. Summary of the invention

[0004] In view of the above technical problems, the present invention provides a conductive slurry for film material transfer and a preparation method, application, and solar cell. The present invention adjusts the organic carrier ratio of the slurry to obtain a better filling capacity of the slurry, and can adapt to molds with extremely narrow line widths to obtain excellent electrode aspect ratios, and can also overcome the adhesion between the slurry and the film material, thereby obtaining better fluidity and a clean battery surface.

[0005] To achieve the above object, the technical solution of the present invention is: A conductive paste for film material transfer, comprising conductive powder, glass powder and an organic carrier, wherein the organic carrier comprises 0.1-0.5wt% of a binder, 0.5-0.7wt% of silicone oil, 0.1-2wt% of an elastomer, 0-0.5wt% of an additive, 3-7wt% of a solvent and 2-7wt% of a plasticizer, calculated based on the conductive paste; The silicone oil is polymethyl silicone oil or other modified silicone oil, and the elastomer is SEBS (hydrogenated styrene-butadiene block copolymer) or SEBS-modified elastomer or SEPS (hydrogenated styrene-isoprene block copolymer) or SEPS-modified elastomer, and SEBS / SEPS or its modified elastomer is hereinafter referred to as elastomer; The binder includes cellulose acetate butyrate, ethyl cellulose and polyvinyl butyral. The combined binder can enable the slurry to have better rheological properties.

[0006] The silicone oil mass content of the present invention is in the range of 0.5-0.7%. If the amount of silicone oil is too little, the interaction between the resin and the film material is strong, and the risk of slurry residue in the non-groove area is high. If the amount of silicone oil is too high, the compatibility of the slurry will deteriorate, the rigid modulus of the slurry will increase, the flow will deteriorate, and the filling capacity will decrease. SEBS / SEPS or its copolymer can form a microgel with a suitable solvent. Such elastomers have the characteristics of weak viscosity and strong oil absorption. Compared with viscous agents, such elastomers have relatively weak cohesion, and the gel property is conducive to the customized optimization of the rheological properties of the slurry. Furthermore, the mass content of SEBS / SEPS and its modified elastomers can be 0.5-1%, and as the solid content of the slurry decreases, the mass content is further 1-2%, thereby achieving better rheological properties of the slurry under low solid content conditions, matching the film material transfer, and obtaining an excellent aspect ratio even under low solid content conditions.

[0007] Preferably, the molecular weight of the cellulose acetate butyrate is 1w-3w, the molecular weight of the polyvinyl butyral is 1w-3w, and the molecular weight of the ethyl cellulose is 5w-20w. In particular, the polyvinyl butyral of this molecular weight can better disperse the silver powder and glass powder, have suitable wetting properties with the organic film material, reduce the residual silver paste of the film material in the non-groove area, and at the same time match the small molecular weight of cellulose acetate butyrate to improve the fluidity of the paste and the filling capacity of the film material mold. Furthermore, a small amount of high molecular weight ethyl cellulose can help the leveling of the silver paste and improve the flatness of the silver electrode, especially ethyl cellulose with a molecular weight exceeding 10w is more suitable.

[0008] Preferably, the content of cellulose acetate butyrate is 0.1-0.3wt%, the content of polyvinyl butyral is 0.1-0.2wt%, and the content of ethyl cellulose is 0.01-0.2wt%. Further preferably, the content of ethyl cellulose is 0.15-0.2wt%. The adhesive within this range can obtain excellent viscoelasticity, and the overall viscosity content cannot be too low. If it is too low, the slurry will not be cohesive enough and the risk of residue will be high. However, if the overall viscosity content is too high, the silver paste will be very viscous, the risk of residue in the non-filled area of ​​the slurry will also be high, and the fluidity will be poor and the filling rate will be low.

[0009] Preferably, the viscosity of the silicone oil is 5-1000mPaS. Silicone oil within this viscosity range, especially dimethyl silicone oil, has a relatively small molecular weight, a low decomposition temperature, and less silicon residue after high-temperature decomposition, which has less effect on the slurry electrode sintering. At the same time, small molecular weight silicone oil can be freed between the resin molecules of the binder to reduce intermolecular forces, lubricate and help the slurry flow, and improve the slurry filling capacity; further preferably, the viscosity of the silicone oil is 5-100mPaS, and further preferably is 20-100mPaS.

[0010] The silicone oil is selected from any one of dimethyl silicone oil, hydroxy silicone oil, amino silicone oil, alkyl silicone oil, octyl silicone oil, and polyether silicone oil, or a mixture of multiple thereof; further preferably, the silicone oil is selected from a combination of dimethyl silicone oil and amino silicone oil. The combination of dimethyl silicone oil and amino silicone oil can better achieve a balance between the filling capacity of the film mold and the flow of the silver paste. On the one hand, the amino group in the amino silicone oil acts on the hydroxyl group in ethyl cellulose and polyvinyl butyral to reduce the entanglement of the resin and the friction between the resin chains, thereby improving the flow; on the other hand, during the mold filling process, the dimethyl silicone oil is freed to the interface, thereby improving the slippery properties of the slurry and reducing the residual silver paste in the non-groove area.

[0011] Preferably, the solvent is selected from one or more combinations of butyl carbitol acetate, diethylene glycol dibutyl ether, diethylene glycol monobutyl ether or alcohol ester dodecahydrate; The plasticizer is selected from one or more combinations of hexadecyl alcohol ester, dimethyl adipate, pentaerythritol triacrylate, ethyl 2-isobutoxybenzoate, dimethyl phthalate or benzyl benzoate.

[0012] The solvent is butyl carbitol acetate, diethylene glycol dibutyl ether, diethylene glycol monobutyl ether and plasticizer alcohol ester hexadecene, pentaerythritol triacrylate, ethyl 2-isobutoxybenzoate, dimethyl phthalate. The combination can obtain better slurry rheology; diethylene glycol dibutyl ether and alcohol ester hexadecene have weak polarity, which can well inhibit the adhesion between the adhesive and the organic film material to obtain a clean battery surface. At the same time, dimethyl phthalate and ethyl 2-isobutoxybenzoate have good compatibility with SEBS / SEPS, and can obtain an ideal gel structure. At the same time, they have good compatibility with cellulose acetate butyrate, polyvinyl butyral, and ethyl cellulose, thereby obtaining better fluidity. Further preferably, the content of diethylene glycol dibutyl ether is 0.5-1.0wt%, the content of alcohol ester hexadecene is 0.2-1wt%, the content of dimethyl phthalate is 0.5-1.5wt%, and the content of ethyl 2-isobutoxybenzoate is 0.5-1.0wt%.

[0013] Preferably, the auxiliary agent includes a dispersant and a thixotropic agent, the dispersant is selected from one or more combinations of organic acid dispersants, amine dispersants, acrylic dispersants or silicone dispersants, and the thixotropic agent is selected from one or a mixture of polyamide wax or hydrogenated castor oil.

[0014] Preferably, the dispersant may be one or a combination of carboxylic acids or amines such as TDO, ED120, ED420, stearic acid, and dodecylamine; the thixotropic agent may be polyamide wax; Furthermore, the content of the dispersant is between 0.05% and 0.4%, and the content of the thixotropic agent is between 0.05% and 0.3%.

[0015] Preferably, the mass fraction of the conductive powder in the conductive paste is 85-90%, the mass fraction of the glass powder is 1.5-5%, the conductive powder is mainly silver powder, the mass fraction of silver powder is 85-90%, the D50 of silver powder is 1-2 μm, and the silver powder specific gravity is 0.3-0.7 μm. 2 / g, tap density is 5.8-6.5g / cm 3 ; The D50 of the glass powder is 1-2μm, and the glass powder can be a mixture of two or more glass powders of common B-Si-Ba system glass, Pb-Si-B system glass, and Bi-Si-B system glass.

[0016] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned conductive paste for film transfer, wherein the conductive powder, glass powder and organic carrier are fully stirred and mixed to obtain a paste composition; the paste composition is rolled and ground to a fineness of less than 7 μm to obtain a paste precursor; the paste precursor is filtered and dispersed to obtain a conductive paste for film transfer.

[0017] Based on the same inventive concept, the present invention also provides an application of a conductive paste for film material transfer in film material transfer, wherein a transfer film is coated on a battery substrate, and then a mold with a grid line is placed directly above the battery substrate, leaving a grid line groove on the transfer film after demolding, and then the conductive paste is printed into the grid line groove on the transfer film, and the transfer film is sintered and decomposed to obtain a battery electrode.

[0018] Based on the same inventive concept, the present invention further provides a solar cell, comprising a substrate and a grid line formed on the surface of the substrate, wherein the grid line is formed by transferring the above-mentioned conductive paste through a film material.

[0019] Due to the adoption of the above technical solution, the present invention has the following advantages and positive effects compared with the prior art: The present invention achieves better fluidity and promotes the filling of slurry into the area to be filled in the film material by adjusting suitable adhesives, silicone oil and elastomer, thereby achieving a high slurry filling amount in the area to be filled in the gate line, and thus obtaining an excellent gate line aspect ratio. Therefore, the present invention can obtain a better filling capacity of the slurry by adjusting the ratio of organic components in the slurry, and can adapt to molds with extremely narrow line widths to obtain an excellent electrode aspect ratio; on the other hand, through the selection of silicone oil and solvent, the adhesion between the slurry and the film material can be well overcome, and better fluidity can be obtained while obtaining a clean battery surface; at the same time, by controlling the residual amount of ash, the bonding performance between the electrode and the silicon wafer is improved. Compared with the existing silver paste, the paste of the present invention can obtain: a) an excellent aspect ratio, with the battery having very little shading and obtaining a smaller line resistance; b) a lower PA. Due to the characteristics of the film material mold transfer, the height and width of the electrode line can be precisely customized. Under the condition of a fine opening, lower silver consumption also obtains ideal electrical performance; c) a clean battery surface. Through the design of organic components, the slurry has appropriate wettability with the film material, so that there will be no silver paste residue in the non-groove area of ​​the transfer film material, thereby reducing the ineffective silver paste consumption; d) through the selection of small molecule silicone oil, the ash residue of the silicone oil is reduced, and the reliability of the sintering connection between the electrode and the velvet surface is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the process route of film material transfer of the present invention. DETAILED DESCRIPTION

[0021] The present invention is mainly aimed at the technology of film transfer for preparing solar cell grid lines, which is different from the current screen printing technology. Since the current conductive paste is mainly to match the narrow line requirements of screen printing, the organic carrier has high requirements for thixotropy and has a certain influence on flow. The slurry has a relatively low filling rate for the mold, and poor filling may even lead to the risk of grid breakage. In addition, for the film transfer technology, there are certain requirements for the slurry, especially the filling capacity and compatibility with the transfer film material.

[0022] Specific analysis: Ideally, the conductive paste matching the film transfer should have the following characteristics: (1) Appropriate compatibility between the organic system and the membrane material. If the compatibility is too good, the silver paste is more likely to remain in the non-mold area of ​​the membrane material, resulting in a lot of sintered silver debris, and the battery appearance and battery performance deteriorate; if the compatibility is too poor, the silver paste will not spread well on the membrane material, and the silver paste scraping and filling will be hindered; (2) The fluidity of the silver paste system needs to be enhanced. The construction method of the silk-screen electrode requires the silver paste to have a certain thixotropy to form a good aspect ratio. The high thixotropic silver paste system has a relatively weak ability to fill the grooves, and it is easy to form breakpoints in the mold grooves, which manifests as macroscopic battery grid breakage or microscopic mold filling rate is insufficient, resulting in increased sintering line resistance. (3) The silver paste system has low organic ash content, especially the decomposition temperature of silicone oil should be low enough and the amount of Si residue after heating should be small.

[0023] Therefore, the present invention provides a conductive paste specifically for film material transfer technology. By adjusting the organic carrier in the conductive paste, better filling capacity can be obtained to adapt to molds with extremely narrow line widths. The adhesion between the paste and the film material can be well overcome through the selection of silicone oil, and better fluidity can be obtained while obtaining a clean battery surface. At the same time, by controlling the residual ash content, the bonding performance between the electrode and the silicon wafer is improved.

[0024] The following is a further detailed description of a conductive paste for film material transfer, a preparation method, an application, and a solar cell proposed by the present invention in conjunction with the accompanying drawings and specific embodiments. The advantages and features of the present invention will become more apparent from the following description.

[0025] A conductive paste for film material transfer, comprising conductive powder, glass powder and an organic carrier, wherein the organic carrier comprises 0.1-0.5wt% of a binder, 0.5-0.7wt% of silicone oil, 0.1-2wt% of an elastomer, 0-0.5wt% of an additive, 3-7wt% of a solvent and 2-7wt% of a plasticizer, calculated based on the conductive paste; The elastomer is SEBS or SEBS modified elastomer or SEPS or SEPS modified elastomer, the silicone oil is polymethyl silicone oil or other modified silicone oil, the viscosity of the silicone oil is 5-1000mPaS, more preferably, the viscosity of the silicone oil is 5-100mPaS, more preferably 20-100mPaS.

[0026] The mass content of silicone oil is in the range of 0.5-0.7%. If the amount of silicone oil is too little, the interaction between the resin and the film material is strong, and the risk of slurry residue in the non-groove area is high. If the amount of silicone oil is too high, the compatibility of the slurry will deteriorate, the rigid modulus of the slurry will increase, the flow will deteriorate, and the filling capacity will decrease. Silicone oil of this viscosity, especially dimethyl silicone oil, has a relatively small molecular weight, a low decomposition temperature, and less silicon residue after high-temperature decomposition, which has less effect on the slurry electrode sintering. At the same time, silicone oil with a small molecular weight can be freed between resin molecules to reduce the intermolecular interaction force, lubricate and help the slurry flow, and improve the slurry filling capacity. Further preferably, the silicone oil is selected from a combination of dimethyl silicone oil and amino silicone oil. The combination of dimethyl silicone oil and amino silicone oil can better achieve a balance between the filling capacity of the film material mold and the flow of silver paste. On the one hand, the amino group in the amino silicone oil reacts with the hydroxyl group in ethyl cellulose and polyvinyl butyral to reduce resin entanglement and friction between resin chains, thereby improving flow. On the other hand, during the mold filling process, dimethyl silicone oil is freed to the interface to improve the slurry slippery properties and reduce silver paste residue in the non-groove area.

[0027] SEBS / SEPS or its copolymers can form microgels with suitable solvents. Such elastomers have the characteristics of weak viscosity and strong oil absorption. Compared with viscous agents, such elastomers have relatively weak cohesion. The gel property is conducive to the customized optimization of the rheological properties of the slurry. Furthermore, the mass content of SEBS / SEPS or its modified elastomer can be 0.5-1%, and as the solid content of the slurry decreases, the mass content is further 1-2%, achieving better rheological properties of the slurry under low solid content conditions, matching film transfer, and obtaining excellent aspect ratios even under low solid content conditions. Therefore, the conductive silver paste is controlled by the elastomer content, combined with the characteristics of film transfer, the silver paste solid content customization range is large, and can achieve 85%-92%, realizing customized development of cost and performance.

[0028] The binder includes cellulose acetate butyrate, ethyl cellulose and polyvinyl butyral. The combined binder can enable the slurry to have better rheological properties.

[0029] Further preferably, the molecular weight of the cellulose acetate butyrate is 1-3w, the molecular weight of the polyvinyl butyral is 1-3w, and the molecular weight of the ethyl cellulose is 5-20w. In particular, the polyvinyl butyral of this molecular weight can better disperse the silver powder and glass powder, have suitable wetting properties with the organic film material, reduce the residual silver paste of the film material in the non-groove area, and at the same time match the small molecular weight of cellulose acetate butyrate to improve the fluidity of the paste and the filling capacity of the film material mold. Furthermore, a small amount of high molecular weight ethyl cellulose can help the leveling of the silver paste and improve the flatness of the silver electrode, especially ethyl cellulose with a molecular weight exceeding 10w is more suitable.

[0030] The content of cellulose acetate butyrate is 0.1-0.3wt%, the content of polyvinyl butyral is 0.1-0.2wt%, and the content of ethyl cellulose is 0.01-0.15wt%. The adhesive within this range can obtain excellent viscoelasticity. The overall viscosity content cannot be too low, otherwise the slurry will not be cohesive enough and the risk of residue will be high. However, if the overall viscosity content is too high, the silver paste will be very viscous, the risk of residue in the non-filled area of ​​the slurry will also be high, the fluidity will be poor, and the filling rate will be low.

[0031] Preferably, the solvent is selected from one or more combinations of butyl carbitol acetate, diethylene glycol dibutyl ether, diethylene glycol monobutyl ether or alcohol ester dodecahydrate; The plasticizer is selected from one or more combinations of hexadecyl alcohol ester, dimethyl adipate, pentaerythritol triacrylate, ethyl 2-isobutoxybenzoate, dimethyl phthalate or benzyl benzoate.

[0032] The solvent is butyl carbitol acetate, diethylene glycol dibutyl ether, diethylene glycol monobutyl ether and plasticizer alcohol ester hexadecene, pentaerythritol triacrylate, ethyl 2-isobutoxybenzoate, dimethyl phthalate. The combination can obtain better slurry rheology; diethylene glycol dibutyl ether and alcohol ester hexadecene have weak polarity, which can well inhibit the adhesion between the adhesive and the organic film material to obtain a clean battery surface. At the same time, dimethyl phthalate and ethyl 2-isobutoxybenzoate have good compatibility with SEBS / SEPS, and can obtain an ideal gel structure. At the same time, they have good compatibility with cellulose acetate butyrate, polyvinyl butyral, and ethyl cellulose, thereby obtaining better fluidity. Further preferably, the content of diethylene glycol dibutyl ether is 0.5-1.0wt%, the content of alcohol ester hexadecene is 0.2-1wt%, the content of dimethyl phthalate is 0.5-1.5 wt%, and the content of ethyl 2-isobutoxybenzoate is 0.5-1.0wt%.

[0033] The slurry was prepared according to the mass ratio of the conductive slurry listed in Table 1 and the preparation method. The specific preparation method is as follows: The conductive powder, glass powder and organic carrier in Table 1 were fully stirred and mixed, and stirred under high shear force for 0.5 hours to obtain a paste composition; the paste composition was repeatedly rolled and ground with different roller spacings on a three-roll mill until its fineness was below 7 μm to obtain a slurry precursor; the slurry precursor was filtered through a sieve, degassed and dispersed to obtain a conductive slurry.

[0034] Table 1 Conductive paste ratios of Examples 1-5 and Comparative Examples 1-2 Note: Silicone oil 1000 in the table is dimethyl silicone oil with a viscosity of 1000mPaS, silicone oil 100 is dimethyl silicone oil with a viscosity of 100mPaS, and silicone oil 10 is dimethyl silicone oil with a viscosity of 10mPaS.

[0035] The above conductive paste is used as Figure 1 The film transfer method shown is used to prepare the grid line electrode of the solar cell, specifically: a transfer film of organic material is coated on the cell silicon substrate, and then a mold with a grid line is placed directly above the cell substrate, leaving a grid line groove on the transfer film after demoulding, and then the conductive paste in the above-mentioned embodiment and comparative example is printed into the grid line groove on the transfer film, the number of grid lines is 196, and then passed through a belt sintering furnace, the transfer film is decomposed during the sintering process, the sintered conductive paste is cooled to form a grid line electrode, and then light injection and laser assisted sintering are performed. In addition, the performance tests of the solar cells and grid lines prepared by each embodiment and comparative example are shown below, and the test results are shown in Table 2.

[0036] Test method: (1) Printing and electrode height and width testing The width, height and aspect ratio of the electrode were measured using an optical microscope and a micro-imaging instrument. Each group of slurry was tested 6 times and the average value was taken.

[0037] (2) Battery conversion efficiency test Under the condition of 1 sun light intensity, the formed solar cells were placed in IV test to measure the electrical performance, including Voc (open circuit voltage), Isc (short circuit current), FF (fill factor), Eff (conversion efficiency). Each slurry was tested for 12 sets of electrical performance data and the average value was taken.

[0038] Table 2 Performance test of solar cells and grid lines prepared in Examples 1-5 and Comparative Examples 1-2 Compared with Examples 1-5, the silicone oil content of Comparative Example 1 exceeds the reasonable range. Compared with other examples, the binder selection of Comparative Example 2 is inappropriate, the binder does not contain polyvinyl butyral and cellulose acetate butyrate, and the compatibility of benzyl benzoate with the adhesive resin is poor. Examples 1-5 can respectively correspond to the differences in silicone oil brands, binder types and ratios.

[0039] Regarding the silicone oil content, compared with Examples 1-5, the comparative example has significant gate breaking, the dimethyl silicone oil content and type are not appropriate, the silicone oil has poor compatibility with diethylene glycol dibutyl ether, and the benzyl benzoate has poor compatibility with the solvent. The conductive paste has a high rigidity modulus, is hard and brittle, has weak filling capacity, and the local filling is not satisfactory, resulting in gate breaking. Compared with other embodiments, the comparative example 2 has an unreasonable binder type, deteriorated slurry fluidity, and poor filling capacity. Although gate breaking does not occur, the FF is relatively low, the electrical performance is poor, and silver paste debris residues appear in the non-groove area.

[0040] Comparing Example 1 with Example 2, Example 2 reduces the viscosity of silicone oil, obtains a better film filling effect, and FF is significantly optimized; Comparing Example 2 with Example 3, Example 3 reduces the content of long-chain ethyl cellulose and increases it to cellulose acetate. Compared with ethyl cellulose, cellulose acetate has a short resin chain and less entanglement, which enhances the fluidity of the slurry, improves the filling capacity, and evenly sintered electrodes, and further improves FF; Comparing Example 3 with Example 4, after amino silicone oil replaces dimethyl silicone oil in Example 4, the filling capacity is further improved, and FF is optimized; Example 5 is relatively Example 4, and the binder is fine-tuned. By reducing the content of polyvinyl butyral and reducing the cellulose acetate butyrate in the system, the fluidity of the slurry is enhanced, the filling capacity is improved, and the FF is improved. Considering the mode of film transfer electrode forming, even if the slurry viscosity is reduced, as long as the amount of resin is reasonable and the sintering activity of the silver powder is matched, the electrode aspect ratio will not differ much.

[0041] Therefore, the present invention provides a conductive paste that can be used for film transfer. The comprehensive performance of the battery obtained through testing can reach the same comprehensive electrical performance as that obtained by existing screen printing. Furthermore, the use of film transfer to produce solar cell grid lines can reduce the amount of battery paste used. Compared with the screen printing method, PA can be reduced by more than 10%, thereby reducing the cost of battery production. The actual electrode width is reduced to ≤15um, the aspect ratio exceeds 50%, the electrode collapse and epitaxy are less, and the photoelectric efficiency is increased by more than 0.05%.

[0042] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Even if various changes are made to the present invention, if these changes fall within the scope of the claims of the present invention and their equivalents, they still fall within the protection scope of the present invention.

Claims

1. A conductive paste for film transfer, comprising conductive powder, glass powder and an organic carrier, characterized in that: The organic carrier includes 0.1-0.5 wt % of adhesive, 0.5-0.7 wt % of silicone oil, 0.1-2 wt % of elastomer, 0-0.9 wt % of additive, 3-7 wt % of solvent, and 2-7 wt % of plasticizer, calculated based on the conductive paste; The silicone oil is polymethyl silicone oil or other modified silicone oil, and the elastomer is SEBS or SEBS modified elastomer or SEPS or SEPS modified elastomer; The adhesive includes cellulose acetate butyrate, ethyl cellulose and polyvinyl butyral.

2. The conductive paste for film transfer according to claim 1, characterized in that: The content of the cellulose acetate butyrate is 0.1-0.3wt%, the content of the polyvinyl butyral is 0.1-0.2wt%, and the content of the ethyl cellulose is 0.01-0.2wt%.

3. The conductive paste for film transfer according to claim 1, characterized in that: The molecular weight of the cellulose acetate butyrate is 1-3w, the molecular weight of the polyvinyl butyral is 1-3w, and the molecular weight of the ethyl cellulose is 5-20w.

4. The conductive paste for film transfer according to claim 1, characterized in that: The viscosity of the silicone oil is 5-1000 mPaS.

5. The conductive paste for film transfer according to claim 1 or 4, characterized in that: The silicone oil is selected from any one of dimethyl silicone oil, hydroxy silicone oil, amino silicone oil, alkyl silicone oil, octyl silicone oil, polyether silicone oil or a mixture of multiple thereof.

6. The conductive paste for film transfer according to claim 5, characterized in that: The silicone oil is selected from a mixture of dimethyl silicone oil and amino silicone oil.

7. The conductive paste for film transfer according to claim 1, characterized in that: The solvent is selected from one or more of butyl carbitol acetate, diethylene glycol dibutyl ether, diethylene glycol monobutyl ether, dimethyl phthalate or alcohol ester dodecaphosphate; and / or The plasticizer is selected from one or more combinations of hexadecyl alcohol ester, dimethyl adipate, pentaerythritol triacrylate, ethyl 2-isobutoxybenzoate, and benzyl benzoate.

8. The conductive paste for film transfer according to claim 1, characterized in that: The auxiliary agent includes a dispersant and a thixotropic agent. The dispersant is selected from one or more combinations of organic acid dispersants, amine dispersants, acrylic dispersants or silicone dispersants. The thixotropic agent is selected from one or a mixture of polyamide wax or hydrogenated castor oil.

9. The conductive paste for film transfer according to claim 1, characterized in that: The mass fraction of the conductive powder is 85-90%, and the mass fraction of the glass powder is 1.5-5%.

10. A method for preparing a conductive paste for film transfer according to any one of claims 1 to 9, characterized in that: The conductive powder, the glass powder and the organic carrier are fully stirred and mixed to obtain a paste composition; the paste composition is rolled and ground to a fineness of less than 7 μm to obtain a slurry precursor; The slurry precursor is filtered and dispersed to obtain a conductive slurry for film material transfer.

11. Use of the conductive paste for film transfer according to any one of claims 1 to 9 in film transfer, characterized in that: A transfer film is coated on a battery substrate, and then a mold with a grid line is placed directly above the battery substrate. After demoulding, a grid line groove is left on the transfer film. Then, the conductive paste described in any one of claims 1 to 9 is printed into the grid line groove on the transfer film, and the transfer film is sintered and decomposed to obtain a battery electrode.

12. A solar cell, characterized in that: It comprises a substrate and a gate line formed on the surface of the substrate, wherein the gate line is formed by transferring the conductive paste according to any one of claims 1 to 9 through a film material.

Citation Information

Patent Citations

  • Transfer method of solar cell grid lines and solar cells

    CN111987175B

  • Coining process of solar cell grid line electrode pattern

    CN105742380A

  • Solar cell grid line transfer printing method and solar cell

    CN111987175A

  • Conductive paste for laser transfer printing and preparation method and application thereof

    CN115083659A

  • High-elastic conductive paste and preparation method and application thereof

    CN116153558A